2020
DOI: 10.1002/jcp.29737
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics with ameliorating effects on the severity of skin inflammation in psoriasis: Evidence from experimental and clinical studies

Abstract: Experimental and clinical studies have confirmed safety and the medical benefits of probiotics as immunomodulatory medications. Recent advances have emphasized the critical effect of gastrointestinal bacteria in the pathology of inflammatory disorders, even, outside the gut. Probiotics have shown promising results for curing skin‐influencing inflammatory disorders through modulating the immune response by manipulating the gut microbiome. Psoriasis is a complex inflammatory skin disease, which exhibits a microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 117 publications
(168 reference statements)
0
17
0
4
Order By: Relevance
“…and Staphylococcus spp. are important components of the skin microbiome ( Grice et al., 2009 ; Mrázek et al., 2019 ), and some studies have confirmed their positive roles in regulating skin immune balance by generating active metabolites ( Mu et al., 2018 ; Atabati et al., 2020 ). Studies have reported that Lactobacillus and Staphylococcus modulate skin immunity by producing active metabolites such as lipoteichoic acid and prevent the adhesion and colonization of pathogens ( Cogen et al., 2008 ; Bodera and Chcialowski, 2009 ; Lai et al., 2009 ; Atabati et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Staphylococcus spp. are important components of the skin microbiome ( Grice et al., 2009 ; Mrázek et al., 2019 ), and some studies have confirmed their positive roles in regulating skin immune balance by generating active metabolites ( Mu et al., 2018 ; Atabati et al., 2020 ). Studies have reported that Lactobacillus and Staphylococcus modulate skin immunity by producing active metabolites such as lipoteichoic acid and prevent the adhesion and colonization of pathogens ( Cogen et al., 2008 ; Bodera and Chcialowski, 2009 ; Lai et al., 2009 ; Atabati et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Commensal microbiota on the skin are involved in both innate and adaptive immunity and maintain the integrity of the skin barrier against pathogens ( Cogen et al., 2008 ; Dréno et al., 2016 ; Zhai et al., 2018 ; Chaudhari et al., 2020 ; Flowers and Grice, 2020 ). For instance, Lactobacillus acidophilus secretes antibacterial agents on the skin and prevents the adhesion of pathogens, whereas Staphylococcal species can inhibit the Toll-like receptor-dependent pathway and modulate inflammation on the skin ( Coconnier et al., 2000 ; Lai et al., 2009 ; Atabati et al., 2020 ; Williams et al., 2020 ). Major technical and analytical breakthroughs have enabled scientists to investigate the microbiome at the genetic level, and studies have demonstrated that the influence of nonculturable microorganisms on the skin ecosystem is often underestimated ( Chen et al., 2018 ; Flowers and Grice, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that oral administration of Lactobacillus pentosus GMNL-77 could effectively treat skin inflammation due to imiquimod treatment in mice. The researchers further found that Lactobacillus pentosus GMNL-77 also ameliorated erythematous scaling lesions in psoriatic mice due to imiquimod treatment [ 104 ]. This experiment provided a theoretical basis for probiotic products to improve psoriasis.…”
Section: Probiotics Gut Microbiome Immunity and People’s Lifementioning
confidence: 99%
“…Probiotics are defined as live microorganisms with healthy beneficial to host if up taken in adequate amounts [ 10 , 11 ]. Recent advances have highlighted the beneficial outcome in the pathology of inflammatory disorders after using gastrointestinal bacteria therapeutically [ 12 ]. Much evidence suggests that probiotic uptake has beneficial effects on blood glucose through different mechanisms [ 13 16 ].…”
Section: Introductionmentioning
confidence: 99%